2023
DOI: 10.1038/s41598-023-29303-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal forecasting of vertical track alignment with exogenous factors

Abstract: To ensure the safety of railroad operations, it is important to monitor and forecast track geometry irregularities. A higher safety requires forecasting with higher spatiotemporal frequencies, which in turn requires capturing spatial correlations. Additionally, track geometry irregularities are influenced by multiple exogenous factors. In this study, a method is proposed to forecast one type of track geometry irregularity, vertical alignment, by incorporating spatial and exogenous factor calculations. The prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…With the goal of providing synthetic alternatives to the known TM-based routes to sutezolid, the literature preparations for TM were reevaluated with an eye for potential modifications that would avoid the direct synthesis and isolation of TM. One early synthetic report in particular described a ring-closing reaction between diethanolamine (DEA) and sodium sulfide, making use of mesylate for hydroxyl activation (Scheme A) . This chemistry suggested that a similar sulfide treatment of dimesyl intermediate 5 may provide an attractive alternative route to a known intermediate sutezolid (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the goal of providing synthetic alternatives to the known TM-based routes to sutezolid, the literature preparations for TM were reevaluated with an eye for potential modifications that would avoid the direct synthesis and isolation of TM. One early synthetic report in particular described a ring-closing reaction between diethanolamine (DEA) and sodium sulfide, making use of mesylate for hydroxyl activation (Scheme A) . This chemistry suggested that a similar sulfide treatment of dimesyl intermediate 5 may provide an attractive alternative route to a known intermediate sutezolid (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
“…One early synthetic report in particular described a ring-closing reaction between diethanolamine (DEA) and sodium sulfide, making use of mesylate for hydroxyl activation ( Scheme 2 A). 19 This chemistry suggested that a similar sulfide treatment of dimesyl intermediate 5 may provide an attractive alternative route to a known intermediate sutezolid ( Scheme 2 B). A major advantage of this chemistry is that DEA and sodium sulfide are low-cost raw materials, which make them ideal structural building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…We experimentally compared two methods for inputting the maintenance intervention records in LSTM using synthetic a) E-mail: kawa@faculty.chiba-u.jp DOI: 10.1587/transfun.2023EAL2019 data. One is the concatenation of maintenance intervention records and health data and feeding them into LSTM [4]. A concatenation method is a straightforward approach to deep learning.…”
Section: Introductionmentioning
confidence: 99%